In-situ stress orientation and main controlling factors of deep shale reservoirs in the second member of Paleogene Funing Formation in Gaoyou Sag, Subei Basin - Zeyu YAN; Bing LIANG; Yaxiong SUN; Hongliang DUAN; Xuming QIU (Shiyou shiyan dizhi, 2024)
The shale oil resources in the second member of the Paleogene Funing Formation in the Gaoyou Sag, Subei Basin exceed 700 million tons. However, the complex geological conditions of both its structure and stress significantly impact the shale oil exploration and development in this area. In particular, the lack of clarity regarding the present-day in-situ stress orientations constrains the deployment of horizontal well groups and the design and optimization of fracturing projects. In this study, the applicability of various methods for interpreting in-situ stress orientations in deep shale reservoirs was investigated based on data from regional focal mechanism solutions, specialized logging, and microseismic monitoring of horizontal well fracturing, as well as the experimental analysis such as velocity anisotropy and paleomagnetic tests. The distribution characteristics of the present-day in-situ stress in the Huazhuang area were identified, and their influencing factors were analyzed. The results indicated that the present-day maximum horizontal principal stress direction in the second member of the Funing Formation mainly ranged from 40° to 55°, with an average azimuth of 45°, indicating a northeastward orientation. In the planar view, the in-situ stress orientation in the study area exhibited minor stress deviations on a larger regional scale, mainly influenced by the structural patterns. Furthermore, stress perturbation zones were found near faults, where stress deviations were more pronounced, and the width of these perturbation zones was positively correlated with fault displacement and extension length. Comparative analysis suggested a decreasing applicability of microseismic monitoring, induced fractures/wellbore collapses, core measurements, and array acoustic anisotropy. Specifically, the velocity anisotropy in array acoustic logging was significantly influenced by lithological phase transitions on a planar scale. Based on the interpretation of stress orientations and the dominant trends of natural fractures, the recommended horizontal well deployment azimuth for this area is SE155° to SSE170°.